EvidenceNOW: Balancing Primary Care Implementation and Implementation Research - Meyers, David (Ann Fam Med, 2018)
The mission of the Agency for Healthcare Research and Quality (AHRQ) is to generate knowledge about how America’s health care delivery system can provide high-quality care, and to ensure that health care professionals and systems understand and use this evidence. In 2015 AHRQ invested in the largest primary care research project in its history. EvidenceNOW is a $112 million effort to disseminate and implement patient-centered outcomes research evidence in more than 1,500 primary care practices and to study how quality-improvement support can build the capacity of primary care practices to understand and apply evidence. EvidenceNOW comprises 7 implementation research grants, each funded to provide external quality-improvement support to primary care practices to implement evidence-based cardiovascular care and to conduct rigorous internal evaluations of their work. An independent, external evaluator was funded to conduct an overarching evaluation using harmonized outcome measures and pooled data. The design of EvidenceNOW required resolving tensions between implementation and implementation research goals. EvidenceNOW is poised to develop a blueprint for how stakeholders can invest in strengthening the primary care delivery system and to offer a variety of resources and tools to improve the capacity of primary care to deliver evidence-based care. Federal agencies must maximize the value of research investments to show improvements in the lives and health of Americans and the timeliness of research results. Understanding the process and decisions of a federal agency in designing a large clinical practice transformation initiative may provide researchers, policy makers, and clinicians with insights into future implementation research, as well as improve responsiveness to funding announcements and the implementation of evidence in routine clinical care.